Cryptosporidium parvum virus 1 genome sequences from pediatric diarrhea cases in coastal Kenya - Agoti, C.N.; Njeru, Regina; Mwanga, M.; Mutunga, M.; Shah, S.P.; Chu, T.-Y.; Nokes, D.J.; Cotton, M.; Phan, M.V.T. (American Society for Microbiology, 2025)
We report nine nearly complete Cryptosporidium parvum virus 1 genome sequences (both segments) recovered from stool samples of pediatric diarrhea patients admitted to Kilifi County Hospital, coastal Kenya. This will be an important resource for monitoring C. parvum infections in humans.